2020
DOI: 10.1111/aji.13323
|View full text |Cite
|
Sign up to set email alerts
|

Are different markers of endometrial receptivity telling us different things about endometrial function?

Abstract: Problem: To what extent do endocrine, immunological, gene expression and histological markers of endometrial receptivity correlate? Method of study: Between November 2017 and September 2019, 121 women referred to a University Hospitals Fertility Clinic consented to inclusion in this cohort study. The women underwent timed endometrial biopsy followed by blood samples in a hormone-substituted cycle. Of these, 37 women had just started IVF treatment, and the remaining 84 had experienced recurrent implantation fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
(88 reference statements)
1
11
0
1
Order By: Relevance
“…15 It was reported that only 4.7% of RIF were without displaced or pathological WOI, 15 although the number varied between different research groups. 13,28,29 Regarding immune profiling, only 17.2% of RIF and 19.5% of RM patients showed no endometrial dysregulation. 16 In line with this evidence, our results showed that nearly 80% of multiple implantation failure patients had a displaced WOI and endometrial immune dysregulation independently or simultaneously.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…15 It was reported that only 4.7% of RIF were without displaced or pathological WOI, 15 although the number varied between different research groups. 13,28,29 Regarding immune profiling, only 17.2% of RIF and 19.5% of RM patients showed no endometrial dysregulation. 16 In line with this evidence, our results showed that nearly 80% of multiple implantation failure patients had a displaced WOI and endometrial immune dysregulation independently or simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, another group found that the ERA results were correlated with the CD56 + NK cell counts, but not CD16 + NK cells, CD163 + Macrophage, and FOXP3 + Treg. 28 The variance in CD56 + NK cells may be due to different study populations' inconsistency and quantification methods. A correlation was found when CD56 was analyzed as a categorical variable or only existed in two extremes (pre-receptive and post-receptive) in their study when CD56 was analyzed as continuous variables.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glucocorticoids seem to increase the activity of regulatory T cells and decrease the cytotoxicity of NK cells simultaneously. However, recent studies on immune regulation have suggested that these regulatory activities could be individualized for each respective cell rather than being regulated in the manner of general suppression by glucocorticoids [ 65 , 66 ].…”
Section: Glucocorticoids and Immune Modulationmentioning
confidence: 99%